Warming‐Induced Effects on Microbial Communities and Nitrogen Cycling Capacity in Tundra Litter Are Modulated by Herb Abundance and Litter Quality - Mathilde Jeanbille; Karina E. Clemmensen; Jaanis Juhanson; Anders Michelsen; Juha Alatalo; Elisabeth J. Cooper; Greg H. R. Henry; Annika Hofgaard; Robert D. Hollister; Ingibjörg S. Jónsdóttir; Kari Klanderud; Anne Tolvanen; et al. (Global Change Biology, 2025)
Climate warming is changing tundra vegetation in the Arctic, with implications for plant litter properties. Warming may thus modify bacterial and fungal communities and their nitrogen (N) cycling capacity in the litter layer, which in turn can affect plant N availability. To address potential warming effects, we characterized the responses of bacterial and fungal communities and their genetically encoded capacity for inorganic N‐transformations in the litter layer, as well as 15 N natural abundance in the underlying soil layer as an integrated measure of N processes in the soil, in 16 long‐term alpine and Arctic tundra warming experiments distributed across 12 circumpolar locations. Although abundance, diversity, and composition of microbial communities were structured by the local conditions rather than experimental warming, warming indirectly modified microbial communities and their capacity for N transformations through changes in litter quality. Specifically, experimental warming resulted in stronger connections between the capacity for nitrification, denitrification and N‐fixation in the litter and the δ 15 N signature in the soil. These warming‐induced connections were mainly mediated by increased dominance of herbs but also increased litter mass. These findings suggest accelerated inorganic N cycling in the litter layer with warming, particularly coupled to local abundance of herbs, which can create positive feedback on plant growth as well as ecosystem respiration. Thus, microbial communities in the litter may contribute to an intensification of ongoing vegetation shifts across the tundra biome.